Sociology of Law Perspectives on Security, Population, and Local Wisdom Issues - Syamsuddin Pasamai; Aan Aswari (Susbtantive Justice International Journal of Law, 2023)
This study aims to provide an overview of governance that always links the interests of society and the State based on the values of the sociology of Law. Therefore, state administrators always pay attention to issues of Security, population, and local wisdom on a country basis. The conceptual study presents this manuscript as an effort to understand how Law is developed and changed along with social and cultural changes. This article explains the basic argument that Pancasila is still the guardian in the development of Law, and it is also proven that there is a development of Law which has a tendency and begins to show detachment from Pancasila values, but in its journey efforts are made to adapt it to Pancasila values in order to reduce the symptoms. Social conflict. Thus concluding that Security, population, and local wisdom are part of influencing the quantity, quality, mobility, and administration of population.